Wiretapping Woes. - Upson, S. (IEEE spectrum)
After the U.S. Congress passed the landmark wiretapping law, law enforcement officers now could conduct a wiretap centrally on a carrier's network by duplicating a phone call digitally and directing the copy to police headquarters. Starting on 14 May, the 1994 law, the Communications Assistance for Law Enforcement Act (CALEA), will also apply to some voice over Internet Protocol providers (VoIP), and the U.S. Federal Bureau of Investigation has asked that it eventually be extended to all Internet-based communications. With this law, the VoIP providers have the ability to route calls over the traditional telephone network, even if only some calls end up traveling that way.